THE ANATOMY OF STIPULES: CASE STUDIES IN DIFFERENT TYPES OF STIPULES - Kamilah, Annida; Ermayanti, Ermayanti; Santri, Didi Jaya (BRIN Publishing (Penerbit BRIN), 2025)
Stipule is an organs in plants that are small in size and usually located at the base of leaf. This research aims to determine the anatomical characteristics of stipules in seven plants with different types of stipules. The study was conducted using descriptive qualitative method. The anatomical preparations of stipules were made using two techniques: the free-hand section method to obtain paradermal sections and the paraffin method to obtain transverse sections. Based on the observation of anatomical structure, it is known that the types of constituent tissues in stipules resemble the types of constituent tissues in leaves, namely: cuticle, upper epidermis, palisade parenchyma, spongy parenchyma, vascular bundles, and lower epidermis Breadfruit (Artocarpus altilis (Parkinson) Fosberg), Cempedak (Artocarpus integer (Thunb.) Merr.), and Rubber Plant (Ficus elastica Roxb. ex Hornem). The parenchyma is found in homogen arrangement in The Noni/Morinda citrifolia L.) and Roses (Rosa indica L.) plants, whereas in Coffee (Coffea canephora Pierre ex A. Froehner) and Sandbox Tree (Hura crepitans L.) plants no vascular bundles were found.